МОЛОДІЖНА ПОЛІТИКА ЄВРЕЙСЬКИХ НАЦІОНАЛЬНИХ ПАРТІЙ (20-ТІ РОКИ ХХ ст.) (Zaporizhzhia Historical Review, 2021)
A new economic policy led to the revival of capitalist groups and to the strengthening of the petty bourgeoisie. This fact intensified the struggle between political parties for the young people. The Jewish national parties of Ukraine tried to bring under their control the movement of the youth by creating and renewing the youth unions and criticizing the environmental policy. The poor welfare standards of the youth and difficulties of the Komsomol development were also used. KP(b)U and KSMY led a severe struggle for working young people and tried to bring peasants and students to the side of the Soviet Union powers. As a result of this struggle the national parties and their youth unions had disappeared from the political scene of Ukraine by the middle of 1920-s.